Positioning a mid-size overseas bank to do business in the USA - Mendelson, Avner (Henry Stewart Talks, 2016)
In this interview Mr Avner Mendelson, President and CEO of Bank Leumi USA discusses positioning his bank to do business in the USA. He describes its scale, the business it does, the segments it targets, the business it no longer does, its operations and profitability. At the centre of its strategy is ‘relationship banking’ and the opportunity to ‘cross-sell’. He describes his ‘ideal customer’ and how the bank pursues new business, as well as the regulatory environment for mid-size banks created in the post-great recession environment.